Kebijakan Tax Amnesty Dalam Sistem Ekonomi Islam - Nandang Ihwanudin (ISLAMICA, 2016)
Tax amnesty is the abolition of tax on the taxpayer because it has violated the payment of taxes by paying ransom on the subject of the tax in accordance with the prevailing provisions, thus avoiding administrative sanctions and criminal penalties. As a policy issued in the form of Law Number 11 Year 2016 on Tax Forgiveness, this policy resulted in the pros cons in the community. Even Muhammadiyah plans to submit a judicial review of the Act. This research will discuss more deeply about how tax amnesty policy toward state income and how the Islamic economic system looks at the enactment of tax amnesty policy. In conclusion, the 2016 tax amnesty policy targets the state revenue from this program to reach Rp. 165 trillion, if this is not achieved then the budget deficit will rise and the debt will definitely increase. Therefore, to achieve these targets, required the readiness of the tax apparatus / program. If the target is achieved then macro-economic growth will increase. Furthermore, the tax amnesty policy according to the Islamic view should be seen first about the tax law in Islam itself, when the tax policy is applied as a permissible, the tax amnesty policy can be issued, but the application of tax amnesty seems hard to find in the Islamic economic system, when tax imposition is set as an additional source to cover the shortfall in state spending.